PENINGKATAN HASIL BELAJAR PEMBELAJARAN TEMATIK SUBTEMA KOMPONEN EKOSISTEM MENGGUNAKAN PENDEKATAN SCIENTIFIC PADA SISWA KELAS V SD NEGERI 107467 GUNUNG PARA KECAMATAN DOLOK MERAWAN KABUPATEN SERDANG BEDAGAI - Hartati, Risma (Jurnal Ilmiah Aquinas, 2022)
This type of research is classroom action research on social studies subject matter with the sub-theme of ecosystem components in class V SD Negeri 107467. The purpose of this research is to improve and/or improve learning practices in schools. The data collection tools used in this study were observation sheets and tests. Based on the learning outcomes in the pre-cycle, it was found that the average student was 65.75 with the number of students who completed 7 while in the first cycle an average of 67 was obtained with the students who completed 9. The learning outcomes of Cycle II with improvements in the implementation of learning in teacher activities were obtained 80% with a good category and the results of the implementation of learning on student activities obtained an average of 75.75 with a good category, individual learning completeness is 18 students. Learning outcomes using a scientific approach to the sub-theme of ecosystem components in class V SD Negeri 107467 Gunung Para District. Dolok Merawan Kab. Serdang Bedagai shows a significant approach.